RESPON PEMBERIAN PUPUK ORGANIK CAIR LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Ikbal Driantama; Hilwa Walida; Widya Lestari (UNIVERSITAS LABUHANBATU, 2021)
Cayenne pepper (Capsium frutescens L.) is a holticulture plant that has many benefits, among others, for consumption, industrial materials and livestock. Efforts to increase chili production through intensification and extensiveness are always accompanied by the use of fertilizers. The potential of organic waste, especially in urban areas with very high dense populations, decomposition of organic waste will produce material rich in elements needed by plants so it is very good to be used as organic fertilizer. This research was conducted in Ujung Padang, Village Ulumahuam, Silangkitang District, South Labuhanbatu Regency, North Sumatra Province in March to May 2019. This study used the method of flat data analysis and used 3 treatments with 10 repeats and was analyzed descriptively. The purpose of this study was to find out the response of LOF household waste in cayenne pepper plant plants (Capsium frutescens L.). From this study showed that the parameters of high and number of plant leaves (cm) with the treatment of liquid organic fertilizer (LOF) household waste showed a high response to the treatment of P1 (50 ml LOFHousehold Waste), then P2 (100 ml LOF Household Waste) and lastly P0 (without LOF treatment).Keywords: Cayenne pepper, household waste, liquid organic fertilizer.